Julia de Burgos : la creación de un ícono Puertorriqueño - Pérez Rosario, Vanessa (University of Illinois Press, 2022)
"Vanessa Pérez-Rosario examines poet and political activist Julia de Burgos's development as a writer, her experience of migration, and her legacy in New York City, the poet's home after 1940"--